Studi Perbandingan Hukum Perlindungan Konsumen Di Indonesia dan Tiongkok - Axel Imanuel Tania; Jennifer Almelia Lim; Chae, Suhan; Thalia Jamiana Kuang (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Consumer Protection is an essential aspect of legal systems, aimed at safeguarding consumer rights in transactions and ensuring fair market practices. This study aims to compare the consumer protection frameworks in Indonesia and China, focusing on regulatory structures, enforcement mechanisms, and their impact on consumer welfare. Using a normative legal research method, the study examines laws, regulations, and related legal principles governing consumer rights in both countries. The findings reveal significant differences in the approaches to consumer protection: Indonesia emphasizes dispute resolution through mediation and arbitration under the Consumer Protection Act (Law No. 8 of 1999), while China relies heavily on administrative enforcement and penalties under the Consumer Rights Protection Law. This comparative study highlights the strengths and weaknesses of each legal system, providing insights into their effectiveness in addressing consumer issues in a rapidly changing global economy.